PERAN BADAN PEMERIKSA KEUANGAN DALAM MENGAWAL TRANSPARANSI ANGGARAN PENDAPATAN BELANJA NEGARA DI ERA DIGITAL - Putri , Nadila; Pratama, Inka Nusamuda; Auzandika, Irgi; Khoirunnida, Hibby; Hamidi, Izzudin; Aulia, Firli; Riansyah, Riansyah; Gunawan, Sahril; Andi, Andi; Putra, Rizki Mandala (Nusantara Hasana Journal, 2025)
The purpose of this study is to determine and analyze the role of the Supreme Audit Agency in guarding the state budget in the digital era. This type of research uses a systematic literature review method, by collecting data from various relevant literature sources. The findings show that the application of digital technology in overseeing the state budget has increased the efficiency and effectiveness of the BPK, including in detecting potential irregularities and increasing transparency of state finances through digital platforms. BPK's transparency portal also allows the public to participate in oversight, which has an impact on increasing accountability and decreasing corruption cases. Recommendations from this study are the need to increase the digital competence of BPK auditors and the equalization of technological infrastructure to support more effective supervision.